Relative age and maturation selection biases in academy football - Hill, M.; Scott, S.; Malina, R. M.; McGee, D.; Cumming, S. P. (Journal of Sports Sciences, 2020)
This study examined the simultaneous effects of relative age and biological maturity status upon player selection in an English professional soccer academy. A total of 202 players from the U9 to U16 age groups, over an eight-year period (total of 566 observations), had their relative age (birth quarter) and biological maturity (categorised as late, on-time or early maturing based upon the Khamis-Roche method of percentage of predicted adult height at time of observation) recorded. Players born in the first birth quarter of the year (54.8%) were over-represented across all age groups. A selection bias towards players advanced in maturity status for chronological age emerged in U12 players and increased with age; 0% of players in the U15 and U16 age group were categorised as late maturing. A clear maturity selection bias for early maturing players was, however, only apparent when the least conservative criterion for estimating maturity status was applied (53.8% early and 1.9% late maturing in the U16 age group). Professional football academies need to recognise relative age and maturation as independent constructs that exist and operate independently. Thus, separate strategies should perhaps be designed to address the respective selection biases, to better identify, retain and develop players.